Integrasi Kurikulum Muhammadiyah Boarding School dan Implikasinya pada Pembelajaran Pendidikan Agama Islam di SMA Muhammadiyah - Ilham Putri Handayani; Muh. Wasith Achadi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2022)
This study explores the integration model of the Muhammadiyah Boarding School (MBS) curriculum and its implications for Islamic Religious Education (PAI) learning in Muhammadiyah High Schools. This research is qualitative, in which observation, interviews, and documentation were used to obtain the data collection method. The key informants for this study were the director, vice principal for curriculum, teachers, and students. The results of this study showed two things. First, the integration of the MBS curriculum at Muhammadiyah High Schools took the form of institutional integration between formal, informal, and non-formal education. Second, the implications of the integration of the MBS curriculum in learning Islamic Religious Education (PAI) were implemented in three aspects: aspects of lesson planning (classes, time, materials, and learning resources), aspects of learning implementation (accommodating four 21st century skills, religious insight, integral personality), and evaluation aspects that balance the assessment of the three domains (cognitive, psychomotor, affective).